2021
DOI: 10.1590/acb360206
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous application of allogeneic adipose-derived mesenchymal stem cell in dogs submitted to minimally invasive plate osteosynthesis of the tibia

Abstract: Purpose To evaluate clinical outcome following minimally invasive plate osteosynthesis (MIPO) associated with percutaneous transplantation of allogeneic adipose-derived mesenchymal stem cells (AD-MSC) at the tibial fracture site in dogs. Methods Thirty-six dogs presenting with nonarticular complete tibial fracture were included in this study. All fractures were treated by the same MIPO technique. The animals were divided in group 1 (n = 20) received a percutaneous appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The T1 results agree with a similar study evaluating the effect of ADSCs on bone healing in dogs undergoing tibial tuberosity advancement surgery; however, the authors did not show significant differences between the treated group and the control group in the subsequent follow-up (60 days) [80]. Franco et al [81] reported that the use of minimally invasive plate osteosynthesis (MIPO) in association with ADSC administration stimulated bone healing after a tibia fracture. They had promising results because, in their study, clinical bone healing occurred on average 28.5 and 70.3 days after treatment, respectively, in the stem cell and control groups.…”
Section: Discussionsupporting
confidence: 85%
“…The T1 results agree with a similar study evaluating the effect of ADSCs on bone healing in dogs undergoing tibial tuberosity advancement surgery; however, the authors did not show significant differences between the treated group and the control group in the subsequent follow-up (60 days) [80]. Franco et al [81] reported that the use of minimally invasive plate osteosynthesis (MIPO) in association with ADSC administration stimulated bone healing after a tibia fracture. They had promising results because, in their study, clinical bone healing occurred on average 28.5 and 70.3 days after treatment, respectively, in the stem cell and control groups.…”
Section: Discussionsupporting
confidence: 85%
“…The T1 results agree with a similar study evaluating the effect of ADSCs on bone healing in dogs undergoing tibial tuberosity advancement surgery; however, the results did not show significant differences between the treated group and the control group in the subsequent follow-up (at 60 days) [ 83 ]. Franco et al [ 84 ] reported that the use of minimally invasive plate osteosynthesis (MIPO) in association with ADSC administration stimulated bone healing after a tibial fracture. They reported promising results: in their study, clinical bone healing occurred on average 28.5 and 70.3 days after treatment, respectively, in the stem cell and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue-derived mesenchymal stem cells (ADSCs) exhibit high expansion potential in vitro, making them useful in stem-cell-based therapies and tissue engineering 7 9 . ADSCs have been reported to treat musculoskeletal disorders which do not respond to conventional treatment 10 , such as osteoarthritis 11 , 12 , injuries of the tendo-ligamentous apparatus 13 , 14 , and bone fractures 15 , 16 in companion and large animals.…”
Section: Introductionmentioning
confidence: 99%